Implementasi Fatwa DSN-MUI Tahun 2002 Tentang Rahn Dalam Layanan Pegadaian Syariah Tuban: Telaah Terhadap Penerapan Biaya Mu’nah - Moh Agus Sifa'; Ahmad Syakur (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study examines the implementation of the 2002 DSN-MUI Fatwa on Rahn in Pegadaian Syariah Tuban services, focusing on the application of mu'nah fees. This study aims to understand how Pegadaian Syariah Tuban applies sharia principles in Rahn services and how mu'nah fees are determined and charged to customers. The results of the study indicate that Pegadaian Syariah Tuban has implemented Rahn in accordance with sharia principles and the provisions of the DSN-MUI Fatwa, with mu'nah fees charged to customers based on the estimated value of marhun. This study contributes to the understanding of the implementation of sharia principles in sharia financial services and can be a reference for practitioners and researchers in the field of sharia finance